Culture and power in traditional Siamese government - Englehart, Neil A., 1964- (Southeast Asia Program Publications, Southeast Asia Program, Cornell University, 2001)
A broad reevaluation of Siam's political culture as it existed prior to King Chulalongkorn's administrative reforms in the nineteenth century. Englehart offers evidence to show that traditional Siamese government functioned more effectively and rationally than most scholars have acknowledged.
Keywords: Thailand -- Politics and government -- 19th century.; Political culture -- Thailand.; Thaïlande -- Politique et gouvernement -- 19e siècle.; HISTORY -- Asia -- Southeast Asia.; POLITICAL SCIENCE -- History & Theory.; Political culture; Politics and government; Thailand; Culture politique -- Thaïlande.; 1800-1899